2015
DOI: 10.1111/ijd.12793
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of clofazimine and pentoxifylline in type 2 lepra reaction: a double‐blind, randomized, controlled study

Abstract: Pentoxifylline effectively reduces initial severity; clofazimine provides sustained improvement but acts slowly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Systemic corticosteroids are the important drugs for the treatment of Type 1 reaction [12]. Presentation of Type 2 reactions can be varied ranging from mild disease to severe systematic disease [13] and are difficult to manage [14]. Type 2 reactions are also treated with analgesics and corticosteroids [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic corticosteroids are the important drugs for the treatment of Type 1 reaction [12]. Presentation of Type 2 reactions can be varied ranging from mild disease to severe systematic disease [13] and are difficult to manage [14]. Type 2 reactions are also treated with analgesics and corticosteroids [8].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid steroid-related adverse events, steroid sparing agent is required for the management of Type 2 lepra reactions [14]. One of such agents is chloroquine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentoxifylline is used as 3 * 400 mg. In a study that compares the efficacy of clofazimine and pentoxifylline, pentoxifylline effectively reduced the initial severity, while clofazimine showed a slow but sustained effect [94]. Resistant erythema nodosum leprosum cases that treated successfully with methotrexate, infliximab and etanercept have been reported [95][96][97].…”
Section: Type 2 Reactionmentioning
confidence: 99%
“…There have been eight small, randomised treatment studies of ENL since the introduction of MDT [912, 15–17]. Only 269 patients were enrolled into these studies and just three studies with a total of 53 participants reported allocation concealment and blinding [15, 16]. Determining outcome measures for clinical studies in complex, multisystem disorders such as ENL is difficult.…”
Section: Introductionmentioning
confidence: 99%